Photocatalytic nanomaterials: Applications for remediation of toxic polycyclic aromatic hydrocarbons and green management - Vishal Dutta; Jyothis Devasia; Ankush Chauhan; Jayalakshmi M; Vasantha V L; Ayush Jha; Aatika Nizam; Kun-Yi Andrew Lin; Suresh Ghotekar (Chemical Engineering Journal Advances, 2022)
Nanomaterials (NMs) have piqued the attention of scientists and researchers across many biomedical sciences due to their superior physical, chemical, and magnetic properties. The efficacy and efficiency of NMs depend on adapting to specific site conditions and soil composition. NMs have lately received much attention in the context of polycyclic aromatic hydrocarbons (PAHs) polluted soil remediation and water mitigation because of their unique properties resulting from their nanoscale sizes. The remediation of hazardous PAHs in water and soil is a hot research subject. Because the exposure of PAHs in water and soil results in pollution, which raises major human health concerns. The current review reports novel advancements in NMs that subsidize enhancement for degradation of PAHs. Challenges to the fabrication of high activity-based photocatalytic materials are also discussed. Furthermore, this review delivers exclusive and wide-ranging perspectives on the fabrication of nanomaterial-based photocatalytic systems. The knowledge of both soil remediation and water mitigation is also updated.